2010
DOI: 10.1042/bst0380841
|View full text |Cite
|
Sign up to set email alerts
|

A pore way to die: the role of mitochondria in reperfusion injury and cardioprotection

Abstract: In addition to their normal physiological role in ATP production and metabolism, mitochondria exhibit a dark side mediated by the opening of a non-specific pore in the inner mitochondrial membrane. This mitochondrial permeability transition pore (MPTP) causes the mitochondria to breakdown rather than synthesize ATP and, if unrestrained, leads to necrotic cell death. The MPTP is opened in response to Ca(2+) overload, especially when accompanied by oxidative stress, elevated phosphate concentration and adenine n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
243
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(253 citation statements)
references
References 273 publications
6
243
0
4
Order By: Relevance
“…Two opening states of the pore have been distinguished, a permanent or long‐lasting state which is associated with cell death, and a transient opening state having a physiological role by providing a pathway to release ROS and calcium from mitochondria which is also regulated by CypD (Elrod et al., 2010; Hausenloy, Wynne, Duchen, & Yellon, 2004; Petronilli et al., 1999). The mPTP is now considered to be central in numerous conditions such as heart, brain, or liver ischemia–reperfusion (Friberg & Wieloch, 2002; Halestrap, 2010; Kim, He, Qian, & Lemasters, 2003; Morin, Hauet, Spedding, & Tillement, 2001; Rauen & de Groot, 2004), drug‐induced liver injury (Jaeschke, McGill, & Ramachandran, 2012), age‐related neurodegenerative diseases (Rao, Carlson, & Yan, 2014), and accumulating data imply the mPTP in organ dysfunction occurring during aging (Hepple, 2016; Rocha‐Rodrigues et al., 2013; Toman & Fiskum, 2011). Conversely, caloric restriction, which is a proven strategy to delay aging and age‐related disease (Balasubramanian, Howell, & Anderson, 2017), is associated with the inhibition of mPTP opening (Amigo, Menezes‐Filho, Luévano‐Martínez, Chausse, & Kowaltowski, 2017; Hofer et al., 2009; Kristal & Yu, 1998; Menezes‐Filho et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Two opening states of the pore have been distinguished, a permanent or long‐lasting state which is associated with cell death, and a transient opening state having a physiological role by providing a pathway to release ROS and calcium from mitochondria which is also regulated by CypD (Elrod et al., 2010; Hausenloy, Wynne, Duchen, & Yellon, 2004; Petronilli et al., 1999). The mPTP is now considered to be central in numerous conditions such as heart, brain, or liver ischemia–reperfusion (Friberg & Wieloch, 2002; Halestrap, 2010; Kim, He, Qian, & Lemasters, 2003; Morin, Hauet, Spedding, & Tillement, 2001; Rauen & de Groot, 2004), drug‐induced liver injury (Jaeschke, McGill, & Ramachandran, 2012), age‐related neurodegenerative diseases (Rao, Carlson, & Yan, 2014), and accumulating data imply the mPTP in organ dysfunction occurring during aging (Hepple, 2016; Rocha‐Rodrigues et al., 2013; Toman & Fiskum, 2011). Conversely, caloric restriction, which is a proven strategy to delay aging and age‐related disease (Balasubramanian, Howell, & Anderson, 2017), is associated with the inhibition of mPTP opening (Amigo, Menezes‐Filho, Luévano‐Martínez, Chausse, & Kowaltowski, 2017; Hofer et al., 2009; Kristal & Yu, 1998; Menezes‐Filho et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…were treated with the calcium ionophore A23187, which is a well described inducer of necrotic cell death due to cellular calcium overload and MPTP formation resulting in plasma membrane rupture and LDH release (10,46). We previously reported that A23187 stimulated [ , but we had not monitored cell death (38).…”
Section: ϫ/ϫmentioning
confidence: 99%
“…For example, MPTP formation and necrotic cell death due to calcium accumulation and oxidative stress contribute to ischemia/reperfusion injury of the heart and other organs (9,10). By blocking MPTP formation, CsA protects from myocardial reperfusion injury (15,16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2þ is not the only regulator of PTP and many other factors (oxidative stress, voltage, pH, peptides and a wide array of small molecules) are able to modulate the activity of this pore [66,67,69]. Importantly, several regulators of PTP opening act by modulating the Ca 2þ sensitivity of the pore [66,103]. In addition to being activated by Ca 2þ…”
Section: Mitochondrial Permeability Transition Pore and Cerebral Ischmentioning
confidence: 99%